1997
DOI: 10.1111/j.1432-1033.1997.t01-2-00021.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Anti‐(β2 Microglobulin) mAb to Study Formation of Amyloid Fibrils

Abstract: Three mAbs, IgG,k 1F11, 7B6 and 14H3, were raised against in vitro-self-aggregated &Z-microglobulin. They recognize the native and unfolded forms of the protein and bind its fibrillar form that is present in amyloid tissue. When assayed in fibrillogenesis tests in vitro, mAb 14H3 inhibited fibril formation from m-microglobulin. This mAb recognizes a sequential epitope corresponding to the C-terminal octapeptide, residues 92-99, of /32-microglobulin. By using synthetic peptides it has been found that the integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 20 publications
4
27
0
Order By: Relevance
“…After 2D-PAGE, the proteins in the gel were transferred onto a PVDF membrane as previously described (Stoppini et al 1997). The b2m isoforms were identified with an anti-human b2m polyclonal antibody (Dako) using a chemiluminescent procedure (ECL plus Western blotting detection reagent Amersham Bioscience).…”
Section: Immunoblottingmentioning
confidence: 99%
“…After 2D-PAGE, the proteins in the gel were transferred onto a PVDF membrane as previously described (Stoppini et al 1997). The b2m isoforms were identified with an anti-human b2m polyclonal antibody (Dako) using a chemiluminescent procedure (ECL plus Western blotting detection reagent Amersham Bioscience).…”
Section: Immunoblottingmentioning
confidence: 99%
“…In 1998, Bellotti et al [3] first demonstrated the presence of a partially unfolded β 2 m that could refold reversibly into a N-β 2 m in an amyloid deposit from hemodialysis (HD) patients. Prior to this report, Stoppini et al [4] reported that a monoclonal antibody specific for C-terminal peptides, which are folded inward in a N-β 2 m molecule, could inhibit fibril formation in vitro. In addition, a conformational variant of β 2 m with an unfolded C-terminus was found in amyloid deposits from HD patients using a monoclonal antibody against C-terminal octapeptide of β 2 m [5].…”
Section: Introductionmentioning
confidence: 99%
“…The following materials were obtained from the commercial source given in parentheses: reagents used for immunofluorescence analysis (Tecnogenetics, Becton Dickinson, Pharmingen, Clontech and Dako); mouse isotyping kit and reagents for electrophoresis (Bio-Rad); reagents for cell culture and enzyme immunoassay (ICN, Gibco BRL, Hyclon). mAb 14H3 was prepared as previously described [5]. The recombinant MHCI complex, produced as described by Springer et al [4] was kindly supplied by K. Doering and recombinant human i2-m was prepared as described by Reid et al [6].…”
Section: Methodsmentioning
confidence: 99%
“…Immunological typing of the antibody was accomplished with peroxidase-conjugated rabbit anti-mouse immunoglobulins. The purification of mAb 14H3 from cell culture medium was carried out as previously described [5] by affinity chromatography on a protein G-conjugated Sepharose column. Scatchard analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation